Determination of the 161Tb half-life. (April 2022) - Collins, S.M.; Gilligan, C.; Pierson, B.; Ramirez, N.; Goodwin, M.; Pearce, A.K.; Archambault, B.C.; Haney, M.M.; Regan, P.H.
Abstract: There is significant interest in the use of terbium radioisotopes for applications in cancer therapy and diagnosis. Of these, 161 Tb, as a medium energy beta-emitter, is being investigated as a potential alternative to 177 Lu. The relatively high proportion of conversion electron and Auger electron emissions per decay make 161 Tb an attractive targeted therapeutic. As a product of nuclear fission, 161 Tb is also of importance to nuclear forensics. The standard uncertainty of the current evaluated half-life of 6.89(2) d contributes significantly to the standard uncertainty of any decay corrected activity determination made. Furthermore, the accuracy of this evaluated half-life has been called into question by measurements reported in 2020 at the Institute of Radiation Physics (IRA), Switzerland, who reported a half-life of 6.953(2) d. In the current work, the half-life of the 161 Tb ground state decay has been measured at three independent laboratories located in the United Kingdom and the United States of America for a total of six determinations using three independent measurement techniques; gamma-ray spectrometry, ionisation chamber measurement and liquid scintillation counting. The half-life determined for 161 Tb of 6.9637(29) d confirms the observed 1% relative increase observed by IRA, though the reported half-lives in this work and at IRA are significantly different (ζ-score = 3.1). Highlights: Half-life of 161 Tb measured by three independent radiometric techniques. Six consistent half-life determinations made across NPL, AWE and PNNL. New half-life of 6.9637(29) d supports recent observations of discrepancies in the historic literature.